L’engagement des universitaires africains expatriés dans l’enseignement supérieur en Afrique - Abdoulaye Gueye (Revue d'anthropologie des connaissances)
For more than a decade, the engagement of the African academic diaspora in higher education in Africa has been closely scrutinized in the social science literature. The question is all the more noteworthy given that African universities have been facing unprecedented challenges: a shortage of lecturers to teach the growing cohorts of students and the extremely low proportion of full professors allowed to supervise master’s and Ph.D. candidates are just a few examples. However, this article is derived from our sense of dissatisfaction upon reading the few studies that deal with this question, works that are largely characterized by a lack of empirical rigor. It is built on a body of rich and years-long fieldwork research in four countries in sub-Saharan Africa (South Africa, Ghana, Niger, and Nigeria), as well as interviews with African academics teaching in the U.S. and Canada. Based on a finely-tailored methodology, the article examines the nature of the resources that circulate to African universities from the academic diaspora; it also analyzes the causes of their unequal distribution. The article demonstrates in fine that the African engagement in higher education is not essentially the consequence of their subscription to a prescriptive patriotism. To be sure, the African academic diaspora are willing to contribute to the wellbeing of their continent. But the choice of the resources they share as well as the identity of their colleagues in Africa who directly benefit from these resources reveal that the structural constraints inherent to the academic profession ultimately inform their engagement in Africa.